Production and characterisation of recombinant human chaperonin 10 for treatment of inflammatory disease - Naylor, Dean J.; Hunt, Ben; Guidolin, Angelo; Hey, Allan W.; Bastiras, Stan; de Bakker, Christopher J.; Chin, David Y.; Marquis, Christopher P.; Lambert, Daniel; Howard, Christopher B.; Dobbin, Caroline A.; Mahler, Stephen M. (Process biochemistry (1991), 2015)
•Production of a novel protein based therapeutic for treating inflammatory diseases.•Process productivity improved using specific host strain and gene promoter elements.•Partial codon optimisation of Cpn10 gene reduced molecular variants. Human chaperonin 10 (Cpn10) and chaperonin 60 (Cpn60) fulfil an essential role in mitochondrial protein folding. Cpn10 is located in the mitochondrial matrix; however, it has also been detected in extra-mitochondrial compartments where it has demonstrated anti-inflammatory and immunoregulatory activity, suggesting a potential therapeutic value for the treatment of inflammatory and autoimmune disorders that corresponds with its recently proposed role as a resolution-associated molecular patterns (RAMPs) molecule. Ala-Cpn10, a recombinant, minimally modified Cpn10 synthesised in Escherichia coli, is formulated for use in clinical trials and pre-clinical studies with intravenous or subcutaneous administration. Herein, we report the development of a bioprocess for the production of ∼115g of recombinant human Ala-Cpn10 from a 100L E. coli fermentation with >99% purity (SDS-PAGE), <0.6EUmg−1 endotoxin, <18pgmg−1 DNA and 3.2% molecular variants. This bioprocess was achieved through a careful optimisation of the gene construct, the promoter system and the fermentation process. Recombinant Ala-Cpn10 produced in this process is active as a molecular chaperone indicating correct tertiary and quaternary structure and the stability profile indicates no significant changes with storage as a liquid for at least 3 years at 2–8°C. The results of validated characterisation assays demonstrate that purified Ala-Cpn10 produced using the optimised process reported here is suitable for its intended purpose as an investigational drug product, and this material is currently being tested in a phase II study for efficacy, safety and impact on biomarkers in subjects with mildly active Systemic Lupus Erythematosus (SLE) under US IND 116156.